Unemployment and the Labor Force Participation of Married Men and Women: A Simultaneous Model - Fleisher, Belton M.; Rhodes, George (The Review of Economics and Statistics, 1976)
Belton M. Fleisher, George Rhodes, Unemployment and the Labor Force Participation of Married Men and Women: A Simultaneous Model, The Review of Economics and Statistics, Vol. 58, No. 4 (Nov., 1976), pp. 398-406